Women of the Bible: from text to image - Seijas de los Ríos-Zarzosa, María Guadalupe; Walker Vadillo, Monica Ann (Scriptural traces: critical perspectives on the reception and influence of the Bible, 2022)
"The contributors present an interdisciplinary approach to the representations of women in the Hebrew Bible by focusing on texts, images and gender"--